Higher Order Thinking Skill (HOTS) Analysis of Students of the Institute of Islamic and Arabic Sciences (LIPIA) on Rewriting Ta'bir Books in Book Creator - Madian M. Muchlis; Taufik Hidayat; Ili Yanti (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2023)
Higher Order Thinking Skill (HOTS ا) is a higher order thinking skill that is not only able to remember, understand and explain, but is able to analyze, evaluate and create a problem. HOTS can not only be seen from the work of the questions but can also be seen from the side of creative ability in Arabic material. Rewriting the book "Ta'bir" in the book creator is one of the abilities to think creatively. The method used in this research is descriptive qualitative method. The data source is taken from students majoring in Idad Lughawi, Language Preparation in the form of project results in book creator. The subjects taken were group 2 with the topic "Birrul Walidain". There are three data analysis techniques, namely data reduction, data presentation and conclusion drawing. The result of the research is that it is known that there are innovations made by students in rewriting the book "Ta'bir" as seen from writing vocabulary explanations, adding pictures, adding exercises and adding audio